Rare bird documentation form for Greater Scaup at Big Creek State Park, 1988 - Dinsmore, Stephen J.et al (1988)
Rare bird documentation form for one to two Greater Scaups at Big Creek State Park in Polk County, IA on May 17, 1988. Epson - sheet feed